Anemia management: development of a rapid-access anemia and intravenous iron service - Radia D; Momoh I; Dillon R; Francis Y; Cameron L; Fagg TL; Overl; H; Robinson S; Harrison CN (Dove Medical Press, 2013)
Deepti Radia,1 Ibrahim Momoh,2 Richard Dillon,1 Yvonne Francis,1 Laura Cameron,1 Toni-Lee Fagg,1 Hannah Overland,1 Susan Robinson,1 Claire N Harrison11Haematology Department, Guy's and St Thomas' NHS Foundation Trust, London, UK; 2Bupa Home Healthcare, Harlow, UKAbstract: This article describes the initiation and evolution of the Rapid-Access Anemia Clinic (RAAC) at Guy's and St Thomas' Hospitals, London, UK. This clinic was set up to provide diagnosis and treatment, and to coordinate investigative procedures, where necessary, into the underlying causes of anemia. Initially piloted with anemic preoperative orthopedic patients, the clinic now treats a wide range of conditions, deriving from both internal and external referrals. Treatment includes dietary advice, supplementation with iron, vitamin B12 and folate, and blood transfusion. Most patients at the RAAC need iron replacement, the majority of which require intravenous (IV) iron. Therefore the first-line IV iron-administration protocol is carefully considered to ensure viability of the service and patient satisfaction. Four IV irons available in the UK are discussed, with explanation of the benefits and drawbacks of each product and the reasoning behind the IV iron choice at different stages of the RAAC's development. Costs to the service, affected by IV iron price and administration regimen, are considered, as well as the product's contraindications. Finally, the authors reflect on the success of the RAAC and how it has improved patients' quality-of-treatment experience, in addition to benefiting the hospital and National Health Service in achieving specific health-care mandates and directives. Drawing from the authors' experiences, recommendations are given to assist others in setting up and providing a successful rapid-access anemia service or similar facility.Keywords: hemoglobin, iron deficiency, ferric carboxymaltose, iron sucrose, iron dextran, iron isomaltoside